The perspective of European researchers of national occupational safety and health institutes for contributing to a European research agenda: a modified Delphi study - Gagliardi, Diana; Rondinone, Bruna M; Mirabile, Marco; Buresti, Giuliana; Ellwood, Peter; Hery, Michel; Paszkiewicz, Peter; Valenti, Antonio; Iavicoli, Sergio (BMJ open, 2017)
ObjectivesThis study, developed within the frame of the Partnership for European Research on Occupational Safety and Health joint research activities and based on the frame designed by the 2013 European Agency for Safety and Health at Work (EU-OSHA) study, is the first example of using the points of view of European occupational safety and health (OSH) researchers.The objective is to identify priorities for OSH research that may contribute to the achievement of present and future sustainable growth objectives set by the European strategies.MethodsThe study was carried out using a modified Delphi method with a two-round survey. Each round involved a panel of about 110 researchers representing the network member institutes was selected according to specific criteria, including the ownership of research expertise in at least one of the four macroareas identified by the reference report developed by EU-OSHA in 2013.ResultsThe study identified some innovative research topics (for example, ‘Emerging technological devices’ and ‘OSH consequences of markets integration’) and research priorities (ie, crowdsourcing, e-work, zero-hours contracts) that are not reflected in previous studies of this nature.The absence of any reference to violence and harassment at work among the researchers’ proposals is a major difference from previous similar studies, while topics related to gender issues and electromagnetic fields show a lower importance.ConclusionsThe innovative design of a research priorities identification process, which takes advantage of a large, representative and qualified panel of European researchers allowed the definition of a number of research priorities able to support the inclusion of innovative OSH research issues in the scope of the next European research agenda.